Superior anti-neoplastic activities of triacontanol-PEG conjugate: synthesis, characterization and biological evaluations - Yimeng Zhou; Ning Li; Zhixia Qiu; Xiaoyu Lu; Min Fang; Xijing Chen; Lili Ren; Guangji Wang; Pingkai Ouyang (Drug Delivery, 2018)
Triacontanol (TA, C30H62O), abundantly present in plant cuticle waxes and bee waxes, has been found to display promising anti-neoplastic potentials. As a long chain fatty alcohol, TA possesses limited aqueous solubility, which hinders its medicinal application. To overcome its solubility barrier, a polymer prodrug was synthesized through attaching TA to poly ethylene glycol (PEG), using succinic acid as a linker with bifunctional amide and ester bonds. Anti-neoplastic effects of PEG-TA were assessed in LoVo and MCF7 cells, anti-proliferative and apoptosis-inducing activities were subsequently confirmed in mouse xenograft model. Encouragingly, PEG-TA possessed selective anti-cancer ability. It did not exhibit significant cytotoxicity on normal cells. Mechanistic examination revealed inhibition of NF-κB nuclear translocation, suppression on matrix degradation enzyme and down-regulation of angiogenic signaling might contribute to its anti-malignant effects. Pharmacokinetics clearly indicated PEGylated TA (named as mPEG2K-SA-TA) substantially enhanced TA delivery with increased plasma exposure (19,791 vs. 336.25 ng·mL−1·h−1, p < .001), mean residence time (8.46 vs. 2.95 h, p < .001) and elimination half-life (7.78 vs. 2.57 h, p < .001) compared to those of original TA. Moreover, mPEG2K-SA-TA appeared to be safe in preliminary toxicological assessment. PEGylated TA also emerged as a functional carrier to deliver hydrophobic chemotherapeutic agents, since it readily self-assembled to micelles in aqueous solution with a low critical micelle concentration (CMC, 19.1 µg·mL−1). Conclusively, PEG-TA conjugate displayed superior anti-neoplastic activities and low toxicity, as well as facilitated the delivery of other hydrophobic agents, which appeared to be an innovative strategy for cancer therapy.